Colorectal cancer patients before resection of hepatic metastases - Rosa, F.; Meimarakis, G.; Stahl, A.; Bumm, R.; Hahn, K.; Tatsch, K.; Dresel, St. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: Evaluation of the role of FDG-PET in comparison to conventional staging methods for detecting extrahepatic tumour deposits prior to resection of liver metastases. Patients, Methods: In our prospective study, 58 patients (24 women, 34 men; age 33-81 years) with liver metastases of colorectal carcinoma underwent FDG-PET. Images were acquired in 3D-mode including transmission scans and reconstructed iteratively. For conventional staging all patients underwent abdominal ultrasound, helical computed tomography (CT) of the thorax and abdomen, and colonoscopy/rectoscopy. A preliminary therapeutic decision was established without knowledge of the FDG-PET findings. Thereafter, it was revised or confirmed according to the results of FDG-PET. Results: In 3/58 patients extrahepatic tumour deposits were concordantly identified with both conventional staging methods and FDG-PET. However, in one case, both conventional methods and FDG-PET were false positive regarding pulmonary metastases. In 12/58 patients, nothing but FDG-PET detected extrahepatic tumour masses, which were later confirmed either by histology or follow-up. Conclusion: Our study suggests that in 21% of patients exclusively FDG-PET is an appropriate diagnostic tool to reveal extrahepatic metastases or local recurrence of colorectal carcinoma. Our results demonstrate that FDG-PET provides relevant additional information for accurate therapeutic planning as compared to the conventional combination of staging methods. Therefore, FDG-PET has to exert a decisive influence on the decision for resection of hepatic metastases.
Keywords: PET; FDG; colorectal cancer; hepatic metastases; extrahepatic disease